2022
DOI: 10.1177/2156759x221086747
|View full text |Cite
|
Sign up to set email alerts
|

Antiracism Starts With Us: School Counselor Critical Reflection Within an Multitiered Systems of Support Framework

Abstract: Due to ongoing inequities, discrimination, and injustice, the antiracist movement has gained momentum in all parts of society, including education and school counseling. A foundational aspect of antiracism is self-reflection to increase awareness, identify biases, and build cultural proficiency. Multitiered systems of support (MTSS) is an evidence-based framework widely used throughout K–12 education in the United States to assist with every student’s school-related success. In this article, we propose an anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 62 publications
0
25
1
Order By: Relevance
“…For instance, Mayes and Byrd (2022) developed an antiracist framework for evidence-informed school counseling, encouraging school counselors to (a) co-create safe, humanizing, and affirming schools; (b) interrogate and dismantle oppressive school-based practices; and (c) co-create policies that supplant the dismantled oppressive policies, while intentionally including student and family voices in decision-making processes. Similarly, Betters-Bubon and colleagues (2022) developed a framework for school counselors merging antiracism and MTSS, offering sage guidelines such as (a) engaging in ongoing introspection regarding one’s biases, values, beliefs, and assumptions; (b) identifying culturally disaffirming school, district, and community practices; (c) developing an action plan to supplant culturally disaffirming policies with those that affirm students’ cultures, lived experiences, and identities; and (d) regular, ongoing progress monitoring. Likewise, Edirmanasinghe et al (2022) conceptualized school counselors’ MTSS utility using antiracist and critical race theory lenses.…”
Section: Culturally Sustaining Practicesmentioning
confidence: 99%
“…For instance, Mayes and Byrd (2022) developed an antiracist framework for evidence-informed school counseling, encouraging school counselors to (a) co-create safe, humanizing, and affirming schools; (b) interrogate and dismantle oppressive school-based practices; and (c) co-create policies that supplant the dismantled oppressive policies, while intentionally including student and family voices in decision-making processes. Similarly, Betters-Bubon and colleagues (2022) developed a framework for school counselors merging antiracism and MTSS, offering sage guidelines such as (a) engaging in ongoing introspection regarding one’s biases, values, beliefs, and assumptions; (b) identifying culturally disaffirming school, district, and community practices; (c) developing an action plan to supplant culturally disaffirming policies with those that affirm students’ cultures, lived experiences, and identities; and (d) regular, ongoing progress monitoring. Likewise, Edirmanasinghe et al (2022) conceptualized school counselors’ MTSS utility using antiracist and critical race theory lenses.…”
Section: Culturally Sustaining Practicesmentioning
confidence: 99%
“…First, in considering areas where they can begin to conduct antiracist work, school counselors should develop their own critical consciousness related to racism’s impact on their values, beliefs, and biases. Activities for interrogating school counselors’ own professional identity are detailed by Betters-Bubon and colleagues (2022). School counselors also may hold many different spaces related to antiracist work.…”
Section: Acknowledging the Challenges For Educators And Antiracismmentioning
confidence: 99%
“…With the increased emphasis on antiracism in the United States, including in K–12 education, the TMS school counseling team approached their building administrators, suggesting the need to evaluate their school through an antiracist lens and explicitly acknowledging that: (a) the education system may primarily benefit students identifying with historically privileged populations (i.e., White, Christian, cisgender male, heterosexual, and able-bodied; Mayes, 2021), (b) antiracist work is ongoing, and (c) such work begins by critically examining one’s own values, identities, and biases (Betters-Bubon et al, 2022). The TMS administrators were supportive and asked the school counselors and the MTSS team to work together due to their overlapping focus on school-wide data, systems, and practices (Goodman-Scott et al, 2020).…”
Section: Case Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Scholars have suggested that school counseling programs and the MTSS framework (i.e., RTI, PBIS, and MTSS) share aspects including a multitiered framework for serving all students based on need; the use of data to guide decision-making; evidence-based practices; collaboration with multiple stakeholders; and cultural responsiveness, advocacy, and equity (Goodman-Scott et al, 2016, 2019, 2020; Ockerman et al, 2012; Ziomek-Daigle et al, 2016). More recently, scholars have also recommended aligning school counseling programs and MTSS using an antiracist lens (Betters-Bubon et al, 2022; Edirmanasinghe et al, 2022). Beyond conceptual articles suggesting the school counselor/MTSS alignment, this research line has been expanding.…”
Section: Comprehensive School Counseling Programsmentioning
confidence: 99%